1994
DOI: 10.1021/jo00089a002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Catalytic Effect of Lead on the Reduction of a Zinc Carbenoid with Zinc Metal Leading to a Geminal Dizinc Compound. Acceleration of the Wittig-Type Olefination with the RCHX2-TiCl4-Zn Systems by Addition of Lead

Abstract: Chem. 1960, 25, 1807-1808 and references cited therein. (2) A catalytic amount of impurity in chromium(I1) salt played an important role in the following reaction. (a) Takai, K.; Tagashira, M.; Kuroda, T.; Oshima, K.; Utimoto, K.; Nozaki, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
168
0
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(178 citation statements)
references
References 1 publication
2
168
0
8
Order By: Relevance
“…As an alternative approach, Rainier and co-workers metathesis reaction [9] using the Takai-Utimoto protocol [10] was investigated for constructing the dihydropyran ring. Treatment of (R)-3 with an in situ-generated reduced titanium ethylidene reagent furnished the dihydropyran ring (R)-6 successfully through ethylenation and subsequent metathesis in a single step.…”
mentioning
confidence: 99%
“…As an alternative approach, Rainier and co-workers metathesis reaction [9] using the Takai-Utimoto protocol [10] was investigated for constructing the dihydropyran ring. Treatment of (R)-3 with an in situ-generated reduced titanium ethylidene reagent furnished the dihydropyran ring (R)-6 successfully through ethylenation and subsequent metathesis in a single step.…”
mentioning
confidence: 99%
“…12 In 1994, Utimoto and Takai demonstrated that the presence of lead in a commercially available pyrometallurgy zinc powder (0.040.07%) is a crucial factor for the fast reduction of diiodomethane to the gem-dizinc species. 13 Later we reported a general procedure to prepare a THF solution of 1, 14 and characterized its structure in THF.…”
Section: Coordination Of Bis(iodozincio)methanementioning
confidence: 99%
“…A number of reports have described the olefination of esters using a titanium carbene reagent (e.g., TakaiUtimoto, 11 Tebbe 12 or Petasis 13 ) to provide the corresponding olefinic enol ethers (Figure 2; 5 ¼ 6). Moreover, Iyer and Rainier have reported that direct transformation of olefinic esters to cyclic enol ethers is possible by using a TakaiUtimoto titanium ethylidene reagent.…”
Section: Fmentioning
confidence: 99%